Issues of establishing the permissible discharge levels of 238U to surface waters taking into account its radiation and toxic effects - A. I. Kryshev; T. G. Sazykina; N. N. Pavlova (Радиационная гигиена)
At present, discharges of 238U to surface waters by nuclear industry enterprises are limited by radiation factor. Registration and control of 238U discharges to water bodies is performed in units of radioactivity (Bq/year) according to the current permit for the water discharge of radioactive substances. At the same time, uranium belongs to the 1st hazard class by its chemical toxicity (extremely dangerous chemicals), it has hygienic standard for content in surface waters. A comparison was made for the limitation of 238U intake to surface waters, taking into account radiation exposure and chemical toxicity. Activity concentration of 238U in water was calculated, at which the annual dose for a critical population group from water use would be 0,1 mSv/year (scenario 1 – the water object is used for drinking water supply) or 1 mSv/year (scenario 2 – the water object is not used for drinking water supply). The calculated activity concentrations were expressed in units of mass concentrations and compared with the maximum permissible concentration of uranium in water, established in Russia, 15 mkg/L. It is shown that compliance with the radiation safety norms does not automatically guarantee compliance with the current hygienic standards for limiting the toxic effects of uranium on population and the environment. The concentration of 238U in water producing the annual dose to population 0,1 mSv taking into account all exposure pathways, exceeds the maximum permissible concentration of uranium in water by 15 times. If water body is not used for drinking water supply, the calculated concentration of 238U in water producing the annual dose to population 1 mSv, is higher than the maximum permissible concentration of uranium in water by 1500 times. The restrictions imposed by the current hygienic standards for the chemical toxicity of uranium could reduce the permissible discharge levels of 238U to surface waters. It is necessary to develop environmental quality standards for 238U, taking into account its chemical toxicity, and include them to the system of establishment of permissible discharge limits of radioactive substances.